The antioxidant activities and chemical compounds of Aquilaria crassna, Aquilaria microcarpa, and Gyrinops versteegii leaves growing in Langkat, North Sumatra, Indonesia - RIDWANTI BATUBARA; T. ISMANELLY HANUM; ODING AFFANDI; ELISA JULIANTI; MARIAH ULFA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Batubara R, Hanum TI, Affandi O, Julianti E, Ulfa M. 2022. The antioxidant activities and chemical compounds of Aquilaria crassna, Aquilaria microcarpa, and Gyrinops versteegii leaves growing in Langkat, North Sumatra, Indonesia. Biodiversitas 23: 6619-6628. Agarwood has been cultivated for its wood and leaves in Indonesia. This research aims to determine the potential of the leaves of Aquilaria crassna, A. microcarpa, and Gyrinops versteegii that grow in Langkat as raw materials for antioxidant-rich tea based on their chemical compounds and antioxidant activities. The leaf powder was extracted using ethanol. Bioactive compounds were analyzed by GC-MS, while the antioxidant activity was analyzed by the DPPH method. The results showed that A. crassna leaves contained alkaloids, flavonoids, tannins, steroid/triterpenoid dan glycosides, whereas A. microcarpa leaves contained alkaloids, tannins, saponins, steroid/triterpenoid dan glycosides alkaloids, tannins, and triterpenoids. In comparison, G. versteegii leaves contained flavonoids, tannins, saponins, steroid/triterpenoids, and glycosides. The IC50 values of ethanol extract of A. crassna, A. microcarpa, and G. versteegii leaves were 30.0079, 29.3263, and 31.6304 µg/mL, respectively. The highest chemical compounds of A. crassna, A. microcarpa, and G. versteegii were Cyano, -acetic acid, 1,2,3,4-Cyclopentane Petrol, and Oxacycloheptadec-8-en-2-one Ambrettolide The three species had high antioxidant activity; therefore they are potential sources of antioxidants.